Antibacterial Activity of Flavonoids from Ethyl Acetate Extract of Milk Banana Peel (Musa x paradisiaca L.) - Rita, Wiwik Susanah; Asih, Ida Ayu Raka Astiti; Swantara, I Made Dira; Damayanti, Ni Luh Yuli (HAYATI Journal of Biosciences, 2021)
Infectious diseases caused by Staphylococcus aureus and Escherichia coli can be treated by milk banana peels (Musa × paradisiaca L.). This study aims to reveal  the  antibacterial  activity  of  milk  banana  peel  ethyl  acetate  extract against Staphylococcus aureus and Escherichia coli, and to identify their active compounds.  Extraction  was  conducted  by  maceration  at  room  temperature, followed by partition. Separation was carried out by column chromatography with mobile phase of chloroform: ethyl acetate (7.5:2.5) and stationary phase of  silica gel  60.  Antibacterial assay  was  performed by  well  diffusion method and  identification  of  active  compounds  was  analyzed  by UV-Vis spectrophotometry and LC-MS/MS. Extraction of the peel powder produced methanol extract,  partition of the methanol extract resulted n-hexane, ethyl acetate, n-butanol, and water fractions. Antibacterial activity assay shows that ethyl acetate extract was the most active to inhibit the growth of both bacteria. Separation with column chromatography resulted 5 fractions. Identification of the  most active  fraction  with UV-Vis showed that the isolate gave maximum absorption at λ 339.00 nm (band  I) and λ 262.00  nm (band  II) which were thought to be flavonol (3-OH substituted). Analysis  with LC-MS/MS shows that the most active fraction contained 3-methacrylate flavonols and 3-(furan- 2yl) acrylate flavonols.